PEREMPUAN UNMET NEED DI KABUPATEN LOMBOK TIMUR (Studi Pengaruh Variabel Demografi, Sosial, Ekonomi, Sikap dan Akses pelayanan Terhadap Unmet Need Index Perdesaan dan Perkotaan) - , LALU MAKRIPUDDIN, Prof. Drs. Kasto, MA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aims of this study is to examine the influences of demographic, social, economic, attitude and services-accesses variables on women with unmet-need. It also examine the differences of women with unmet need by area of residence (rural and urban). Research was conducted in East Lombok District, with a survey method, supported by qualitative data. Respondent samples consist of 310 that selected by multistage sampling. The analysis technique used in this study was descriptive analysis and structural equation modeling to test the accuracy of the proposed model. In addition, Z-test calculation was also used for understanding whether there was a difference between women with unmet need in rural and urban areas. Related model among variables, both in rural and urban areas, according to (fit) with empirical data or model declared fit. The model explains: (1) demographic, social, economic, attitudes and services-accesses variables, negatively influence on women with unmet need (unmet need index). (2) The value of Zc as 0,41 (< 1.96), means the average unmet need index, showed no difference between the rural-urban, or no difference women with unmet need of rural and urban areas. The model shows that demographic variable influence on women with unmet need as -0.15 at rural and -0.27 at urban. The influence of social variables, as -0.12 at rural, and -0.23 at urban. Social variables also has positive influence on the attitude, as 0.87 in rural and 0.94 in urban areas. Influence of attitudes variable on women with unmet need, as -0.24 at rural, and -0.12 at urban areas. The influence of economic variables, as -0.54 at rural, and -0.73 at urban areas. Economic variables, also influence positively on services-access variable, at rural areas as -0.96, and at urban areas, as -0.91. Influence of access-services variable on unmet needs of women, at rural areas as -0.36 and -0.14 at urban areas. The existence of women with unmet need, showing that the implementation of programs, has not been able to meet the public demand for family planning. Efforts to overcome them should be a comprehensive manner. The variables that influence, need to intervene so as to reduce the number of women with unmet need in the future. Women who are negative tend to not use contraceptives. While a positive attitude, it would be using contraception, but the ecological factors discourage it, as no reasons of services-access. Women with unmet need are generally low income. Reducing the cost of contraceptives should be a priority, including by ensuring availability of contraceptives. Husband supporting to women for use contraceptives. Nevertheless, ethnic Sasak people, still hold patriarchal ideology. Husband very important role in decision-making. Therefore, women's access to education should be a priority. Education can improve women's role, and influence women's attitudes toward the use of contraceptives, became more positive.